Resonances Engaging Music in Its Cultural Context - Morgan-Ellis, Esther (Open textbook library., 2020)
Welcome to Resonances: Engaging Music in Its Cultural Context! Although this book is intended primarily for use in the college music appreciation classroom, it was designed with consideration for independent learners, advanced high school students, and experienced musicians. That is to say, it includes enough detail that expert guidance is not required and is written using broadly-accessible language. At the same time, it addresses advanced topics and positions music as a serious object of study.